(untitled) (Research, Society and Development, 2020)
Childhood is a phase of life in which children have as their main occupation, playing, this action is essential to maintain their physical and mental health and can include objects and occur individually or in a group. It is worth corroborating that, in childhood, the illness and hospitalization of children are factors that challenge healthy development, since hospitalization allows the manifestation of an early maturation for this phase. The manuscript is a literature review research with a qualitative approach and descriptive character in order to describe the contributions of the therapeutic toy to care for the child in the hospital. After associating all descriptors, 15 articles were selected that maintained coherence with the descriptors and the objectives of the study. After reflective reading, three categories emerged: therapeutic toys and contributions to the hospitalized child; difficulties in inserting therapeutic toys in the care of hospitalized children; therapeutic toys as a subsidy for nursing care for hospitalized children. The therapeutic toy in child hospitalization reduces stress, releases affectivity and allows the child to be able to express his emotions within the hospital environment, being an effective strategy, as the child releases his creativity, reinvents the world and explores its limits. It is concluded that, when confronting the sufferings of the hospitalized child, expressed in the face of pain and in the absence of motivation and human warmth, the therapeutic toy can be used as resources that facilitate and bring out the child’s skills and potential and thus seeks to rescue the importance of toys and playing for the well-being of hospitalized children and their families.